Life-threatening perioperative anesthetic complications: major issues surrounding perioperative morbidity and mortality. Issue 1 (28th August 2017) - Steadman, Joy; Catalani, Blas; Sharp, Christopher; Cooper, Lebron
Abstract : Perioperative morbidity and mortality related to anesthesia involves multiple factors. Patient characteristics and comorbidities play a role in many of these events, highlighting the importance of preoperative screening. While optimization of patient comorbidities is not always possible, having data regarding those comorbidities can prove life-saving. Equipment and medication considerations also enter into untoward outcomes such as anesthetic interventions outside of the traditional operating room where resources are sometimes lacking and haste creates errors. Ultimately, when surgeons and anesthesiologists cooperate in patient care, communicating concisely but thoroughly, patients are more likely to do well. The language of surgeons is that of diagnosis requiring a surgical intervention, while anesthesiologists are discussing patient comorbidities impacted by anesthetic medications, positive pressure ventilation, neuraxial techniques, ramifications of patient positioning, effects of opiates and so on. Because all of the considerations combine in determining outcomes, it is incumbent on both surgeons and anesthesiologists to understand those elements leading to severe morbid events as well as death. This review touches on many of the most important factors.